A case series of pediatric leprosy - Deepika Uikey; Rima Joshi; Nikhil Verma (Wolters Kluwer Medknow Publications, 2020)
Children are believed to be the most vulnerable group to most of the infectious diseases and similar is the case with Mycobacterium leprae infection owing to their weak immunity. Leprosy in children carries an epidemiological significance and can be considered an index of the prevalence of disease. We aim to know the incidence, duration, spectrum, reactions, and deformities in childhood leprosy through this study. Out of the total of 300 leprosy patients, 4% (12) patients belonged to the pediatric age group (<14 yeas) and 288 (96%) patients were adolescent/adults. Family history was present in 25% of the children with leprosy and only 2.47% adults with leprosy. Tuberculoid and borderline tuberculoid were the most common among pediatric patients. Indeterminate leprosy was specifically seen among children. Majority of the pediatric patients were paucibacillary (58.33%). In pediatric patients, two cases of both type 1 and type 2 reactions were seen. Deformities (Claw hand) were seen in 2 (16.67%) children. Leprosy occurs in children in substantial proportion, thus, adequate specific measures should be taken for children in leprosy control.